An AR-based gamified English course in vocational college through interest-driven approach - Wang, Dan; Md Khambari, Mas Nida (Horizon Research Publishing, 2020)
In recent years, augmented reality (AR) technology’s application has been explored in numerous disciplines. Many studies claimed that AR technology had significant advantages in enhancing learning interesting and boosting the understanding and collaborative learning etc. However, in China, most college students lack learning interest and adopt a passive method to learn English. In order to improve the learning situation, the researcher utilized the interest-driven creator (IDC) theory as the basis to design an AR-based gamified English course in vocational college. The study aimed to answer the following questions: (1) How does the AR-based gamified learning environment impact students’ learning motivation in English course? (2) How does the AR-based gamified learning environment impact students’ collaborative learning in English course? This study was conducted in a vocational college of China and the in-depth interviews were adopted to collect data. The results of the investigation revealed that students’ learning motivation was enhanced through the change of teacher’ role and using AR technology’s virtual content. Additionally, the AR-based gamified learning environment can effectively enhance collaborative learning through strengthening the willingness of discussion and providing more opportunities, and the relaxed learning atmosphere.